Pengaruh Penggunaan Arsip Elektronik Terhadap Produktivitas Karyawan (Studi Kasus Pada Kantor UPBU Sultan M. Salahuddin Bima) - Ramadhan Bima Sukmaraga; Mulyadin Mulyadin (Universitas Hamzanwadi, 2021)
This study aims to determine the effect of using electronic records on employee productivity (a case study at the UPBU Sultan M. Salahuddin Bima Office). This type of research is associative using primary data sources from secondary data. The population used in this study were 111 employees at the UPBU Sultan M. Salahuddin Bima office, consisting of 81 Civil Servants (PNS) and 31 contract employees. The sample in this study were 53 employees using the Slovin formula. The sampling technique of this research is using proportionate stratified random sampling technique. The data collection techniques used were observation, interview, questionnaire and literature study. The data analysis technique used is validity test, reliability test, simple linear regression analysis, simple correlation coefficient, determination coefficient and t test. The results show that there is a significant influence between the use of electronic records on employee productivity at the UPBU Sultan M. Salahuddin Bima office with a t-count value of 7,348 greater than the t-table value of 2.008.